Effect of sildenafil on stable chronic heart failure: a prospective randomized-controlled clinical trial - Wael Abdelatief Elhakeem (Journal of Medicine in Scientific Research, 2019)
Background Patients with systolic heart failure (HF) who develop secondary pulmonary hypertension have reduced exercise capacity and increased mortality compared with HF patients without pulmonary hypertension. A defective nitric oxide signaling is involved in left ventricular (LV) diastolic abnormalities and remodeling. Phosphodiesterase type 5 inhibition, by blocking degradation of nitric oxide second-messenger cyclic guanosine monophosphate, might be beneficial. Aim of the study In our study, we tested the effects of phosphodiesterase type 5 inhibition (sildenafil) on LV ejection fraction, diastolic function, pulmonary artery pressure, and clinical status. Patients, methods, and results One hundred HF patients (New York Heart Association classes II–IV) were assigned randomly to placebo or sildenafil (50 mg three times per day) for 6 months, with assessment at the first and 6 months of LV ejection fraction, diastolic function, pulmonary artery systolic pressure, and exercise performance (using 6 min walk test). The two groups studied were similar in terms of age, sex distribution, etiology of cardiomyopathy, the prevalence of chronic atrial fibrillation, LVEDD, LA dimensions, and pulmonary artery pressure as well as drug therapy is given to each group all through the study period (P > 0.05). After 1 month of therapy, there was a significant increase in LV ejection fraction and a decrease in pulmonary artery systolic pressure in the sildenafil group (P < 0.01 and <0.001). In the placebo group, there was no significant change in the LV ejection fraction and pulmonary artery systolic pressure (P > 0.05). Doppler-derived variables of LV diastolic function improved significantly in the sildenafil group (P < 0.05), whereas in the placebo group, there was no significant change in the Doppler-derived diastolic parameters (P > 0.05). Over 6 months of therapy and follow-up, LV ejection fraction increased from 31.5 ± 5.4 to 36.4 ± 3.5 and the difference was not significant between the two groups (P > 0.05), whereas in the sildenafil group, ejection fraction % increased significantly from 30.6 ± 4.5% at baseline to 45.6 ± 5.4% (P < 0.001). There was no significant change in the placebo group in the pulmonary artery systolic pressure (PASP) (P > 0.05), whereas in the sildenafil group, it decreased significantly from 48.3 ± 17.7 to 28.4 ± 6.4 mmHg (P < 0.001). Diastolic measures of LV function showed a sustained improvement after 6 months of sildenafil. The transmitral E wave velocity, A wave velocity, E/A ratio, and isovolumic relaxation time decreased from baseline through 6 months (all P < 0.01), which indicates an improvement in LV diastolic function and a decrease in LV filling pressure. Changes observed at 6 months after sildenafil were significantly different compared with the placebo group (all P < 0.01). The 6 min walking distance showed sustained improvement after 6 months of sildenafil therapy. Also, in the placebo group, there was a significant increase in the walking distance for 6 min. However, the walking distance in the sildenafil group was significantly higher than that of the placebo group,P value less than 0.001. Conclusion In patients with HF, long-term use of sildenafil was well tolerated. This therapeutic regimen (50 mg three times per day) promoted a sustained significant improvement in LV systolic and diastolic function properties in comparison with placebo.